Could Aqueous Film-Forming Foams (AFFFs) and Encapsulator Agents (EAs) Interfere on the Reproduction and Growth of Daphnia similis? - Cara, Álison Luís; dos Santos Barboza Ortega, Andressa; Pusceddu, Fabio Hermes; de Souza Abessa, Denis Moledo [UNESP]; Pereira, Camilo Dias Seabra; Maranho, Luciane Alves (Springer Nature, 2021)
In firefighting of class B, fire suppression agents (FSA), such as aqueous film-forming foams (AFFF) and encapsulating agents (EA), have been used to cool, suppress, and remove the burning surface. However, several studies pointed out the aquatic environment as the destination of perfluorinated compounds and their degradation products. The toxicity of per- and polyfluoroalkyl compounds (PFASs), especially the FSAs, raises environmental health concerns. In this study, the reproduction and body length of the aquatic microcrustaceans Daphnia similis were analyzed through the organisms’ exposure to two FSAs (Cold Fire® Suppressant Agent and Liovac®) in the following dilutions: 0.000093%, 0.0001875%, 0.000375%, 0.00075%, 0.0015%, 0.0003125%, 0.000625%, 0.01025%, 0.025%, and 0.005%, respectively. Our results showed that exposure to FSA caused inhibitory effects on the reproduction of Daphnia similis. The LOEC and NOEC of Cold Fire® were respectively 0.0001875% and 0.000093%, and significant chronic toxicity (p < 0.05) was observed at 0.0015 to 0.0001875% concentrations. The mean body lengths of surviving organisms exposed to all dilutions of Cold Fire® were significantly lower (p < 0.05) than the control organisms. For Liovac®, the respective LOEC and NOEC were 0.005% and 0.0025%. No significant differences were observed (p < 0.05) in the length of the organisms exposed to the Liovac®, compared to the control. The adverse effects on D. similis were observed at concentrations lower than those recommended by the manufacturers. Our results show that FSAs may cause chronic toxicity to freshwater aquatic organisms, posing risk in a real environmental scenario. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Fire suppression agents; Freshwater; Microcrustacean; Perfluorinated compounds; PFAS